2015
DOI: 10.1371/journal.pone.0121073
|View full text |Cite
|
Sign up to set email alerts
|

Shrimp Serine Proteinase Homologues PmMasSPH-1 and -2 Play a Role in the Activation of the Prophenoloxidase System

Abstract: Melanization mediated by the prophenoloxidase (proPO) activating system is a rapid immune response used by invertebrates against intruding pathogens. Several masquerade-like and serine proteinase homologues (SPHs) have been demonstrated to play an essential role in proPO activation in insects and crustaceans. In a previous study, we characterized the masquerade-like SPH, PmMasSPH1, in the black tiger shrimp Penaeus monodon as a multifunctional immune protein based on its recognition and antimicrobial activity … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 21 publications
(9 citation statements)
references
References 48 publications
(95 reference statements)
1
8
0
Order By: Relevance
“…This result is in accord with previous observations in the crayfish P. leniusculus, which revealed that pacifastin transcripts were present during the middle phase of crayfish embryo development (Zhang et al, 2010). In the shrimp P. monodon, the relationship of the expression profiles of proPO, PPAE, and SPH genes during larval development stages has been investigated (Charoensapsri et al, 2011;Jearaphunt et al, 2015). PmPPAE1, PmproPO2, PmMasSPH1, and PmMasSPH2 transcripts were detected during all of the larval stages, whereas PmPPAE2 and PmproPO1 transcripts were primarily expressed during the late stages of larval development (mysis and postlarvae).…”
Section: Expression Profiles Of Pmpacifastin-like Transcripts In Varisupporting
confidence: 89%
See 3 more Smart Citations
“…This result is in accord with previous observations in the crayfish P. leniusculus, which revealed that pacifastin transcripts were present during the middle phase of crayfish embryo development (Zhang et al, 2010). In the shrimp P. monodon, the relationship of the expression profiles of proPO, PPAE, and SPH genes during larval development stages has been investigated (Charoensapsri et al, 2011;Jearaphunt et al, 2015). PmPPAE1, PmproPO2, PmMasSPH1, and PmMasSPH2 transcripts were detected during all of the larval stages, whereas PmPPAE2 and PmproPO1 transcripts were primarily expressed during the late stages of larval development (mysis and postlarvae).…”
Section: Expression Profiles Of Pmpacifastin-like Transcripts In Varisupporting
confidence: 89%
“…Previously, we showed that disruption of PmproPO gene expression could affected the expression of a terminal serine proteinase (PmPPAE2) and a pattern recognition protein (PmLGBP) (Amparyup et al, 2012). Likewise, suppression of PmMasSPH1 also reduced the expression of PmPPAE2 transcripts (Jearaphunt et al, 2015).…”
Section: Effect Of Rnai-mediated Suppression Of Pmpacifastin-like Genmentioning
confidence: 98%
See 2 more Smart Citations
“…The roles of clip domain-containing SPHs characterized in insects ( 15 17 ) and crustaceans ( 46 ) have been almost exclusively restricted to the positive regulation of the PPO cascade where they seem to act as cofactors for the proper cleavage and activation of PPO by PAPs. Although the mosquito CLIPA8 ( 22 ) is thought to fall within this functional category of SPHs, CLIPA2 ( 30 ) negatively regulates PPO activation indirectly by fine-tuning the level of activation of TEP1 in a yet undefined mechanism ( 7 , 24 , 26 , 47 ).…”
Section: Discussionmentioning
confidence: 99%